12=9x-7

Simple and best practice solution for 12=9x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=9x-7 equation:


Simplifying
12 = 9x + -7

Reorder the terms:
12 = -7 + 9x

Solving
12 = -7 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
12 + -9x = -7 + 9x + -9x

Combine like terms: 9x + -9x = 0
12 + -9x = -7 + 0
12 + -9x = -7

Add '-12' to each side of the equation.
12 + -12 + -9x = -7 + -12

Combine like terms: 12 + -12 = 0
0 + -9x = -7 + -12
-9x = -7 + -12

Combine like terms: -7 + -12 = -19
-9x = -19

Divide each side by '-9'.
x = 2.111111111

Simplifying
x = 2.111111111

See similar equations:

| 9a-2=2 | | 0=-3x-5 | | -2n-15=33 | | 2x^2-8x=90 | | 10x-6+90+2x=180 | | 20s+5s= | | 3t^2+t+36=36 | | 3x-3=63 | | 3(5y+7)=-9 | | 2y+5=5y-6 | | 30x+5=25-x | | .20m+3=1.40m | | -74-4a+10b-76-b-6a= | | 3c-4c+1=5c+4+3 | | 3y=-2x-9 | | 12x=52 | | 2X+6Y=18 | | 32-(x+5)=9x-3 | | 3x^2+x-2= | | 32-(x-5)=9x-3 | | 1.14r=6 | | 3y-1=9+y | | X=3x-36 | | 4x+10=13x | | -3=-3x-5 | | X+7=38 | | 10x+20=-30+10x | | 4+x=14 | | 37+k=3(-7k+5) | | 22x+21=-33x-6 | | -6(1-8n)=6n+36 | | -8(t+9)=24 |

Equations solver categories